Implementation of Authentic Assessment on the Theme of the Beauty of My Country - Misnawati, Misnawati (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2020)
This research aims to determine the implementation of Authentic Assessment in the theme of the beauty of my country with the sub-theme of the natural beauty of my country for class students IV Elementary School 68/1 Kembang Paseban. This research uses a descriptive approach qualitative. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions Test the validity of the data using triangulation techniques, namely triangulation of sources, techniques and time. The results of this research indicate that the implementation of authentic assessment in The theme of the beauty of my country with the sub-theme of the natural beauty of my country for class students IV elementary school 68/1 Kembang Paseban is not yet implemented optimally because experienced several obstacles, including several assessment techniques that still exist assessment techniques that have not been implemented, and teachers assume that they exist teacher assessment feels burdened by the many aspects that will be assessed, and feels lack of time to carry out authentic assessments.